Scientific validation of the traditional knowledge of Sikta ("Tabernaemontana sananho", Apocynaceae) in the Canelo-Kichwa Amazonian community - Luzuriaga-Quichimbo, Carmen X.; Ruiz-Téllez, Trinidad; Blanco-Salas, José; Cerón Martínez, Carlos E. (Mediterranean Botany, 2018)
Tabernaemontana sananho is a tree member of the Apocynaceae family referred to as sikta in Kichwa language. It is widely used in northern South America as painkiller, stimulant, antiseptic and is also highly valued as a sacred plant. In this work, we report the traditional knowledge and uses of sikta by the scarcely contacted Kichwa community of Pakayaku (Pastaza province, Ecuador) and further provide a scientific framework for its scientific validation. A review of the available literature revealed the presence of a wealth of biologically active indole alkaloids that potentially account for the great number of medicinal uses of sikta. This case study is illustrative of the importance of scientific validation of traditional knowledge (i) for indigenous communities —as empowering tool—, (ii) for the sake of scientific knowledge and (iii) for plant conservation.